2000
DOI: 10.1002/(sici)1097-0134(20000215)38:3<327::aid-prot8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of mouse and Syrian hamster PrP: Implications for activity

Abstract: Molecular dynamics computer simulations have been performed on Mouse (Mo) and Syrian Hamster (SHa) prion proteins. These proteins differ, primarily, in that the SHa form incorporates additional residues at the C-terminus and also includes a segment of the unstructured N-terminal region that is required for infectivity. The 1-ns simulations have been analyzed by using a combination of dynamical cross-correlation maps, residue-residue contact plots, digital filtering, and residue-based root-mean-square deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
(48 reference statements)
2
15
0
Order By: Relevance
“…The most relevant structural changes involve the destructuration of the C-terminal part of helix B (residues 188-194). Until now it has instead been assumed that HB and HC constitute the stable core of the protein whereas the conformational transition to the b-rich form involves helix A (Parchment and Essex, 2000;Alonso et al, 2001). However the results of our computations are in line with NMR (Donne et al 1997;Zahn et al, 2000) and x-ray (Knaus et al, 2001) data revealing a significant flexibility of the C-terminal end of HB, with a very recent sequence alignment study predicting that the C-terminal residues in HB are frustrated in their helical state (Dima and Thirumalai, 2002), and also with MD simulations by Santini and Derreumaux (2004) which shows that unfolding of HA is not an early step in PrP interconversion and that there is no evidence that HB and HC are more stable than HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most relevant structural changes involve the destructuration of the C-terminal part of helix B (residues 188-194). Until now it has instead been assumed that HB and HC constitute the stable core of the protein whereas the conformational transition to the b-rich form involves helix A (Parchment and Essex, 2000;Alonso et al, 2001). However the results of our computations are in line with NMR (Donne et al 1997;Zahn et al, 2000) and x-ray (Knaus et al, 2001) data revealing a significant flexibility of the C-terminal end of HB, with a very recent sequence alignment study predicting that the C-terminal residues in HB are frustrated in their helical state (Dima and Thirumalai, 2002), and also with MD simulations by Santini and Derreumaux (2004) which shows that unfolding of HA is not an early step in PrP interconversion and that there is no evidence that HB and HC are more stable than HA.…”
Section: Discussionmentioning
confidence: 99%
“…We further investigate this hypothesis in this study, checking how human PrP C globular domain reacts to mildly acidic conditions, i.e., much less acidic than that investigated by Alonso et al (Alonso et al, 2001 and Sekijima et al (2003), in which protonation should involve mainly histidine residues. We tackle this goal by means of molecular dynamic (MD) simulations (van Gunsteren and Berendsen, 1990;Braatz et al, 1992;Fox and Kollman, 1996), which have already been fruitfully used to investigate the dynamical behavior of prion proteins (Zuegg and Gready, 1999;Billeter and Wüthrich, 2000;Parchment and Essex, 2000;Alonso et al, 2001Alonso et al, , 2002DeMarco and Daggett, 2004;Santini and Derreumaux, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is not possible experimentally to determine the mechanism of conversion at high resolution. Two short molecular dynamics simulation studies of PrP C at neutral pH have been reported recently (28,29). Here we present 10-ns simulations of PrP C at neutral and low pH and evaluate the connection between low pH and increases in ␤-structure.…”
mentioning
confidence: 93%
“…The first studies utilizing this technique involved analysis of correlated motions in cytochrome c (McCammon, 1984), ribonuclease A with two different substrates (Brünger et al, 1985), HIV-1 protease (Harte et al, 1990;Harte et al, 1992;Swaminathan et al, 1991), and BPTI (Ichiye and Karplus, 1991). Since these pioneering studies, cross-correlations and DCCMs have been used to analyze the fluctuations of many diverse systems, including proteins (Arcangeli et al, 1999;Parchment and Essex, 2000;Arcangeli et al, 2001;Rizzuti et al, 2001;Young et al, 2001;Luo and Bruice, 2002;Zoete et al, 2002), protein-nucleic acid complexes (Suenaga et al, 2000;Trylska et al, 2005), and enzymes (Bahar et al, 1997;Radkiewicz and Brooks III, 2000;Rod et al, 2003;Sulpizi et al, 2003;Agarwal, 2004;Gunasekaran and Nussinov, 2004;Schiøtt, 2004;Wong et al, 2004;Fuxreiter et al, 2005;Gorfe and Caflisch, 2005;Ma et al, 2005). A recent study analyzing both the B1 domain of protein G and ubiquitin suggests the correlated motions obtained from MD simulations agree well with measured NMR data (Lange et al, 2005).…”
Section: Introductionmentioning
confidence: 99%